Incidencia de virosis en el cultivo de sandía (Citrullus lanatus L), en el Ecuador - Vera Mosquera, Jorge Guillermo (2021)
The present bibliographic research was carried out in order to study the different behaviors of viruses in watermelon cultivation in Ecuador, for this, positions of several authors were analyzed, reflected in books, scientific journals, sketches on the Web, etc., Therefore, it was determined that the damage caused by viruses in the watermelon crop appears from the beginning of the vegetative phenological development of the crop and in turn has an impact on its reproductive development; However, there are several methods and techniques, whether chemical, such as; correct dosage of agrochemicals suitable for the control of insect pests and weeds, which act as natural vectors and in addition to this there are also manual controls, such as; placement of colored traps in the cultivation plots, which even acts as an ecological or organic medium, among other methods reflected in this study. Therefore, it was recommended to carry out field days, links with the community, undergraduate and postgraduate thesis, to improve the problem raised as much as possible